Maternal employment and female labor force participation: A case study from Turkey - Değer Eryar; Hasan Tekgüç (Izmir University of Economics, Department of Economics, 2015)
The focus of this paper is to examine the impact of having a working mother on their daughter's labor force participation rate for the first time in Turkey by using a representative sample from the third largest city Yzmir. Our findings indicate that the gender role attitude is one of the most important determinants of women's initial entry into the labor force, especially for those women with lower education levels. However, the same effect loses its significance as a factor in women's decision to remain in the labor force. This result suggests that although the gender role attitude can induce low-educated women to participate in the labor market initially, the lack of adequate work-family reconciliation policies in Turkey seem to adversely affect their decision to stay in the labor force as wives and mothers.
Keywords: J16; J21; Z13; 330; Female labor force participation rate; work-family reconciliation; labor force attachment; gender role attitude; Turkey